Transcriptomic analysis of HEK293A cells with a CRISPR/Cas9-mediated TDP1 knockout - Dyrkheeva, Nadezhda S.; Zakharenko, Alexandra L.; Malakhova, Anastasia A.; Okorokova, Larisa S.; Shtokalo, Dmitry N.; Medvedev, Sergey P.; Tupikin, Alexey A.; Kabilov, Marsel R.; Lavrik, Olga I. (Biochimica et biophysica acta. General subjects, 2024)
Tyrosyl-DNA phosphodiesterase 1 (TDP1) is a human DNA repair protein. It is a member of the phospholipase D family based on structural similarity. TDP1 is a key enzyme of the repair of stalled topoisomerase 1 (TOP1)–DNA complexes. Previously, with the CRISPR/Cas9 method, we obtained HEK293A cells with a homozygous knockout of the TDP1 gene and used the TDP1 knockout cells as a cellular model for studying mechanisms of action of an anticancer therapy. In the present work, we hypothesized that the TDP1 knockout would alter the expression of DNA repair–related genes. By transcriptomic analysis, we investigated for the first time the effect of the TDP1 gene knockout on genes' expression changes in the human HEK293A cell line. We obtained original data implying a role of TDP1 in other processes besides the repair of the DNA–TOP1 complex. Differentially expressed gene analysis revealed that TDP1 may participate in cell adhesion and communication, spermatogenesis, mitochondrial function, neurodegeneration, a cytokine response, and the MAPK signaling pathway. •Transcriptomic analysis of HEK293A cells with a knockout of the TDP1 gene (TDP1-KO cells) was performed for the first time.•Among DEGs common to three biological replicates of TDP1-KO cells no DNA repair enzymes or factors were found.•We identified DEGs of cell adhesion and communication, spermatogenesis, a cytokine response, the MAPK signaling pathway.